1993
DOI: 10.1089/neu.1993.10.57
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Protection by Moderate Hypothermia Initiated After Experimental Traumatic Brain Injury

Abstract: The effects of postinjury hypothermia on behavioral outcome following moderate fluid percussion traumatic brain injury (TBI) were examined. In Experiment I, three groups of rats were examined. The first group was normothermic (37.5 degrees C); and hypothermia (30 degrees C) was initiated 15 min and 30 min postinjury in the second and third groups, respectively. Whole body cooling was achieved by ventral ice pack. Cooling of the brain to 30 degrees C was achieved in 25 min and maintained for 60 min. Brain tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 18 publications
5
34
1
Order By: Relevance
“…In that study, hypothermia of 338C significantly reduced mortality rates as well as attenuated deficits in beam walking, beam balance, and body weight loss compared to normothermia treatment. In a study by Lyeth et al (1993a), the effects of 1 h post-injury hypothermia (338C) on behavioral outcome was evaluate. Some evidence for improved behavioral outcome was demonstrated with post-traumatic hypothermia.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…In that study, hypothermia of 338C significantly reduced mortality rates as well as attenuated deficits in beam walking, beam balance, and body weight loss compared to normothermia treatment. In a study by Lyeth et al (1993a), the effects of 1 h post-injury hypothermia (338C) on behavioral outcome was evaluate. Some evidence for improved behavioral outcome was demonstrated with post-traumatic hypothermia.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…The beam balance task is one of the most widely used techniques to assess deficits of balance and motor function [24,30,31] in models of cerebellar [32], traumatic [33][34][35][36][37], subarachnoid hemorrhage [16,17,19] and global [31] and focal [30,[38][39][40] cerebral damage. The rats are required to balance steadily on a narrow, usually wooden beam of various diameters and shapes.…”
Section: Beam Balancementioning
confidence: 99%
“…Clifton et al (1991) reported that adult rats treated with transient hypothermia (32°C for 1 h) beginning 5 min after fluidpercussion (F-P) brain injury exhibited better functional outcome (beam walking and beam balance) than normothermic controls. Further work showed that hypothermia also improved behavioral outcome when begun within 15 min, but not 30 min, posttrauma (Lyeth et al, 1993). tex was significantly increased 5 rnin after TBI, returned to control values by 30 min, and was reduced at 1 and 7 days.…”
mentioning
confidence: 90%